Using networked simulation to assess problem solving by tactical teams. - Fletcher, J. D. (Computers in Human Behavior)
Part of a special issue on computer-based performance assessment of problem solving. Assessing problem solving by military tactical teams is a compelling and nationally significant challenge to students of human behavior. Certain processes of problem-solving are more accessible to assessment within teams, because team members must explicitly share and communicate mental representations of the problem solving environment with each other. Networked simulation offers unique opportunities to assess and observe these processes, which have been found to account for a substantial proportion of tactical team success. A framework for use of networked simulation to attain these goals is presented, and it is argued that in order to fulfill its promise for assessing tactical teams, the collection of data in networked simulation must be supplemented with display capabilities, direct observation, communication records, and biographical data.